2021
DOI: 10.14507/epaa.29.5655
|View full text |Cite
|
Sign up to set email alerts
|

Critical policy scholarship in education: An overview

Abstract: This paper presents an overview of critical policy scholarship (CPS) in education. Historically, policy research has been dominated by what is commonly referred to as the policy science tradition, which is positivist in its philosophical stance and instrumentalist in its purpose—it focuses on producing knowledge relevant for policy decisions. However, with the rise of interpretive social inquiry in the 1970s and against the backdrop of unique political developments in the 1980s, CPS emerged as an alternative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
0
8
0
1
Order By: Relevance
“…Our interpretations of the data surrounding TFA -gathered in different ways over multiple years across diverse siteshas supported a general disposition that allows for critique of the organization. Moreover, and in line with the theoretical framing above (e.g., Levinson & Sutton, 2001;Molla, 2021;Shore & Wright, 2011), we do not see TFA (and its international variants) as purely rational solutions to objectively identified problems; therefore, the "shared problems, shared solutions" mantra (see Ahmann, 2015) does not resonate with our understandings of educational policies and the programs with which they are aligned. In fact, we do not view any policies in this manner, but instead understand problems themselves to be discursively created and politically motivated (e.g., Bacchi, 2009).…”
Section: Methodsmentioning
confidence: 67%
“…Our interpretations of the data surrounding TFA -gathered in different ways over multiple years across diverse siteshas supported a general disposition that allows for critique of the organization. Moreover, and in line with the theoretical framing above (e.g., Levinson & Sutton, 2001;Molla, 2021;Shore & Wright, 2011), we do not see TFA (and its international variants) as purely rational solutions to objectively identified problems; therefore, the "shared problems, shared solutions" mantra (see Ahmann, 2015) does not resonate with our understandings of educational policies and the programs with which they are aligned. In fact, we do not view any policies in this manner, but instead understand problems themselves to be discursively created and politically motivated (e.g., Bacchi, 2009).…”
Section: Methodsmentioning
confidence: 67%
“…Geppert, Bauer-Hofmann and Hopmann (2012) stated that the autonomy granted to schools in Austria is growing and that examples, in which the central government affects schools, are decreasing. In addition, Molla (2021) reported that the influence of state and market on education is too big and emphasizes a new way of thinking (critical political research).…”
Section: Discussionmentioning
confidence: 99%
“…CQP researchers make methodological decisions that recognize “the value of methodological rigor , the contextuality of policy and the positionality of the policy analyst [emphasis in original]” (Molla, 2021, p. 4). They employ qualitative research methodologies because such work “never hides behind aggregated numbers, directing itself instead to portray in-depth pictures of actual individuals who operate under various veils of oppression (Lincoln, 2015, p. 198).…”
Section: Conceptualizing Critical Qualitative Policy Researchmentioning
confidence: 99%